Contested Vulnerability: A Case Study of Girls in secure care. (May 2018) - Ellis, Katie
Abstract: Figures from 2015 show that two hundred and five children entered secure accommodation from England and Wales. 47% were placed because they were on remand or sentenced for committing a serious offence. 43% were placed by social services under a child welfare order. The remaining 10% were secured by their local authority on criminal justice grounds. This paper uses the example of girls in secure care to explore understandings that are applied to young people considered 'vulnerable' and 'troublesome' simultaneously. While policy around secure accommodation claims that it offers a therapeutic intervention, to help young people work through their problems and learn appropriate coping mechanisms, it also keeps them 'safe' by physically locking them away from the world in which they have been entrenched. Using detailed ethnographic fieldwork, this paper explores the experiences of girls living in a setting usually exempt from scrutiny and showcases their views of being 'worked with' in an institution designed to enable reform. Significantly, findings show that girls rejected the 'vulnerable' label that was ascribed to them and instead felt that vulnerability was better defined by life experience instead of age. By examining girl's own perspectives of their complex pathways into secure care, this paper will contest the binding of childhood and vulnerability and argue that such an act disenfranchises girls from the services that are designed to help them. Highlights: Participants rejected the 'vulnerable' label that professionals gave them Girls reflected that vulnerability was bound with experience and not age Residents were denied knowledge of 'inappropriate' life experiences. Infantilising young people meant chances to target harmful behaviour were lost. Participants were keen to reach sixteen to escape social work intervention.